Lo sagrado y lo profano en la poesía de Ivonne Gordon [Dossier: Más allá de la literatura: adaptaciones y nuevas formas de expresión cultural en Ecuador (Ponencias del Congreso de la Asociación de Ecuatorianistas, Quito, julio de 2019)] - Rogers, V. Daniel (2020)
This article develops an approach to the poetry of Ecuadorian writer, Ivonne Gordon Vailkis, with an emphasis on her anthology Manzanilla del insomnio (2002). The author draws attention to the use of words and images derived from Hebrew and views Gordon’s poetry as a reflection on the subject of the transgression of linguistic and cultural boundaries drawing on the concept of ‘contact zone’ employed by Mary Louise Pratt. The text examines the marginal status of the poetic voice in this collection of Gordon Vailakis’ poems.